Protective Effect of Curcumin Against the Toxic Effect of Acrylamide on the Rat Hippocampus (may, 10.1007/s44411-025-00171-z, 2025) - Cetin, Seda; Ozbag, Davut; Ogeturk, Murat; Dogan, Zumrut; Annac, Ebru; Dumlupinar, Ebru; Erdemli, Mehmet Erman (Springernature, 2025)
[Abstract Not Available]